Pedagogia dos multiletramentos em um projeto de leitura nos anos iniciais do Ensino Fundamental: construção de base para um projeto de compartilhamento pedagógico - Silva, Nordeci de Lima (2019)
This research aims at understanding a teacher’s pedagogical intervention process, mediated by multiliteracies, in a third-grade group of Elementary School, in the social, historical and cultural context of a school, in order to develop a pedagogical practices sharing proposal amongst teachers. Theorical-methodological foundation is Critical-Collaborative, once it aims at the critical understanding of the social, historical and cultural context of the involved subjects through collaborative actions and pedagogical interventions of multiliteracies practices. Multiliteracies practices spark creativity, dynamism, innovation, interest and motivation for producing senses, decapsulation of pedagogical practices, expansive learning, valuation of student’s social and cultural environment within multimodal, multimedia and multicultural perspectives, with transforming practices. Research has been carried out by the teacher-researcher with a group of third grade students of Elementary School. For procedures of production and collection of data, we have used video, photos, pedagogical activities and reports, which have been analyzed based on a the language of critical reflection: describe, inform, confront and reconstruct. The research results point out changes in the teacher’s pedagogical practice through a reading project aimed at reading and writing literacy. Relevance of this study is justified by the importance of pedagogical practice as continuous education process for teacher development as well as to foster diversity of pedagogical practices in the school context. Understanding of results allowed the development of a multiliteracies pedagogical actions and practices sharing proposal, based on teachers’ critical-collaborative education process